Political Cartel and Political Corruption in Indonesia - Lestari, Yeni Sri (Law Research Review Quarterly, 2016)
The reform system in Indonesia has fostered democratization in the government system. However, the practice of political corruption is also increasingly prevalent among the political elite. the multiparty political system that forms a cartel party is one of the factors that increases the occurrence of political corruption. The cartel party creates a system of cooperation that is able to maintain and regulate the state in accordance with the interests of its groups, especially in finding funding sources that come from state finances. This article aims to determine the relationship between cartel party practices and the perpetuation of political corruption in Indonesia. The role of the cartel party in the occurrence of political corruption is the main subject of this article. To fulfill the purpose of writing in this article, then the example of the Century Bank case scandal involving many political elites will be examined and analyzed more deeply. The qualitative method used in this study was obtained through a literature review. This study found that the cartel party system has given freedom to the form of political corruption, eliminated the system of checks and balances, the death of freedom of speech, and brought false hope to the established democratic system of a state government.